2000
DOI: 10.1111/j.1469-7793.2000.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of renal iron transport in the anaesthetized rat

Abstract: In vivo microinjections of 55FeCl3 were made to assess renal iron (Fe2+/3+) transport in the anaesthetized rat. Following microinjection into proximal convoluted tubules (PCTs), 18·5 ± 2·9 % (mean ± s.e.m., n= 11) of the 55Fe was recovered in the urine. This recovery was not dependent on the injection site indicating that iron is not reabsorbed across the surface convolutions of the proximal tubule. Following microinjection into distal convoluted tubules (DCTs) 46·1 ± 6·1 % (n= 8) of the injected 55Fe was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
80
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 15 publications
4
80
0
Order By: Relevance
“…Since it has been reported in the literature that iron-restricted diets are associated with high renal DMT1 expression and a decrease in urinary iron (34), our evidence of the coincident localization of iron proteins and iron deposits under anemia might indicate the reabsorption of iron from glomerular ultrafiltrate when iron demand is high. The purpose of this mechanism could be the provision of iron to renal cells for their metabolic activity and to help maintain iron homeostasis, emphasizing the importance of renal physiology in hematological processes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Since it has been reported in the literature that iron-restricted diets are associated with high renal DMT1 expression and a decrease in urinary iron (34), our evidence of the coincident localization of iron proteins and iron deposits under anemia might indicate the reabsorption of iron from glomerular ultrafiltrate when iron demand is high. The purpose of this mechanism could be the provision of iron to renal cells for their metabolic activity and to help maintain iron homeostasis, emphasizing the importance of renal physiology in hematological processes.…”
Section: Discussionmentioning
confidence: 89%
“…Although kidney is not usually associated with serum iron balance, several studies found renal DMT1 expression in mice and rats, suggesting that this organ may have a role in iron homeostasis (4,10,33). Furthermore, Wareing et al (34) reported a decrease in urinary iron levels, suggesting iron reabsorption in renal tubules.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Using microperfusion of 55 Fe, Wareing et al (34) demonstrated significant reabsorption of Fe 2ϩ in the LH and that this reabsorption could be mediated by DMT1 (10,34). Thus it is reasonable to conclude that, like with Fe 2ϩ , Cd 2ϩ is transported, at least in part, by DMT1 in the apical membrane of the LH, in its TAL segment where DMT1 has been shown to be present (10).…”
Section: Discussionmentioning
confidence: 99%
“…Since their study, a divalent metal transporter (DMT1) has been cloned (18) and immunolocalized to the apical membrane of the thick ascending limb (TAL), distal tubule (DT), and the cortical collecting tubule (CCT) of the rat nephron (11), suggesting a role for this transporter in the renal handling of divalent metal cations. In a recent study, Wareing et al (34) have clearly demonstrated in the rat that DMT1 can transport Fe 2ϩ along the loop of Henle (LH) and distal tubule. Besides Fe 2ϩ , DMT1 also transports Cd 2ϩ and Zn 2ϩ (18).…”
mentioning
confidence: 99%